Role of positive lifestyle activities on mood, cognition, well-being, and disease characteristics in multiple sclerosis. Issue 4 (4th July 2018) - Strober, Lauren B.; Becker, Alexandra; Randolph, John J.
ABSTRACT: Multiple sclerosis (MS) is a neurological condition associated with a wide variety of physical, cognitive, and mood-related symptoms. While disease-modifying treatment has been shown to reduce the severity and frequency of MS symptom relapses, engagement in certain daily activities holds promise as an adjunctive treatment to better manage disease sequelae. The present study sought to determine whether healthy nutritional choices, exercise, and social/intellectual engagement impacts functioning in individuals with MS. Two hundred and forty-eight (248) MS participants completed a questionnaire assessing factors related to cognitive health (Cognitive Health Questionnaire; CHQ). They also endorsed measures assessing disease symptoms and management, mood, and well-being/quality of life. A measure of information processing speed was administered to a subset of participants. Findings indicated that a previously derived CHQ factor comprised of healthy nutritional habits and exercise items was associated with less fatigue, better sleep, reduced pain, and improved mood and disease management. A factor with items assessing social and intellectual engagement correlated with mood, disease management, and well-being. Endorsement of items in both CHQ factors was associated with better information processing speed. Subsequent regression analyses indicated that education and mood were most predictive of nutritional habits and exercise, while MS self-efficacy was particularly associated with engagement in social and intellectual activities. In sum, these findings suggest that self-reported engagement in healthy lifestyle habits has far-reaching effects on multiple aspects of daily living and disease management in MS.